FRAME OF HIZBUT TAHRIR INDONESIA (HTI) AS A FUNDAMENTALIS GROUP IN THE DISCOURSE OF DEMOCRACY IN ONLINE MEDIA - nfn Karman (Jurnal Penelitian dan Pengembangan Komunikasi dan Informatika, 2015)
Indonesia is a democratic country. Therefore, Indonesia conducts periodic general election every five years since 1955. Indonesia has variety/difersity of culture . That one gives different attitude toward democracy both as a system or as an ideology. One of the attitude is the expression of a rejection against democracy. One of organizations/groups rejecting democracy is Hizb Tahrir Indonesia (HTI). It articulates its rejection to democracy through online media (website). This research tries to find frames on HTI’s websites regarding discourse of democracy. Method of this study is qualitative-content analysis, using agenda setting theory at the second level (level frame). In looking for news, this research used key words: “pemilihan umum/general election”, “demokrasi/democracy”. The result finds four (4) main frames in its websites: (1) the frame of democracy as a tool of capitalism and colonialism; (2) Frame of Indonesian government as an colonialist’s cat’s paw; (3) frame of democracy as a shield of non-Muslims; (4). frame of democracy as a system that make people in misery. In this study, researcher doesn’t dealt with interesting topics because of the limitations of the method/tool used. Therefore, for further studies, it needs to deepen this issue. Coverage of research should not be limited to only HTI but other muslim organizations.Keywords: Frame; Hizbut Tahrir Indonesia; fundamentalist; discourse; democracy.